2008
DOI: 10.1097/cmr.0b013e3282f94651
|View full text |Cite
|
Sign up to set email alerts
|

Changing biology of cutaneous melanoma

Abstract: Survival of patients with cutaneous melanoma (CM) has improved significantly worldwide despite moderate treatment changes. The aim of our study was to determine whether the time period of diagnosis was an independent prognostic factor. The data of 1752 patients diagnosed with CM in Slovenia between 1983 and 1997 were analyzed. Cox proportional hazards model was used to assess the effect of multiple variables on survival. No significant decrease was observed in mean tumor thickness, whereas mean age at the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…3 The parietal pelvic fascia covers the sacral nerves and piriformis muscles, and continues to a fascia covering the ventral surface of the levator ani muscle (Fig 1). 3 The parietal pelvic fascia covers the sacral nerves and piriformis muscles, and continues to a fascia covering the ventral surface of the levator ani muscle (Fig 1).…”
Section: In Replymentioning
confidence: 99%
“…3 The parietal pelvic fascia covers the sacral nerves and piriformis muscles, and continues to a fascia covering the ventral surface of the levator ani muscle (Fig 1). 3 The parietal pelvic fascia covers the sacral nerves and piriformis muscles, and continues to a fascia covering the ventral surface of the levator ani muscle (Fig 1).…”
Section: In Replymentioning
confidence: 99%
“…3 Because treatment of patients with melanoma with regional metastases has unfortunately not changed in the last three decades, we believe that the disease itself has become less aggressive. Our group studied the entire Slovenian population of patients with melanoma using the Slovenian National Cancer Registry, and found that the most important independent predictor of survival among patients diagnosed with CM between 1983 and 1997 was time of diagnosis.…”
Section: Authors' Disclosures Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…Concomitant with this, there has been a shift towards earlier diagnosis, with a consequent improvement in prognosis. This has been ascribed by numerous authors to improved public and professional education [14]. …”
Section: Introductionmentioning
confidence: 99%